Temporally programmed cyclic deformation to control structural hierarchy and shrinkage in poly lactic acid films. (24th January 2023) - Blake, Amy; Cakmak, M.
Abstract: In this paper we explore the role of programmed deformation history on the strain induced crystallization-crystalline order and chain orientation developed in initially amorphous poly lactic acid films in rubbery state. For this purpose, we use highly instrumented programmable uniaxial stretcher that captures true strain, true stress, birefringence continuously during processing. Using this highly instrumented tool, we apply deformation up to strategically selected strain levels where initially amorphous PLA film potentially could strain-crystallize. This is followed by small strain cycling to affect the level of orientation and order in crystalline and amorphous phases through stretch-retract sequence. With application of strain cycling following deformation near strain hardening and beyond, the crystalline chain orientation increases dramatically as the oriented amorphous regions are allowed to relax to form oriented crystals as the number of sites forming crystals increases and unoriented amorphous regions are then oriented in subsequent cycles. Deformation followed by small strain cycling lead to near perfect crystalline chain orientation and high crystallinity but smaller crystallite sizes especially under moderate total strains. For the first time, stretching plus strain cycling the thermal shrinkage in oriented films has been shown to substantially decrease at the same overall strain levels as the fraction of taut oriented amorphous chains reduces while the number of crystalline sites increases substantially leading to a more thermally stable morphology. This opens new processing step that can be employed in large tenter frame biaxial stretching machines together with heat setting to produce thermally stable substrates. Graphical abstract: Image 1 Highlights: In this paper, for the first time we are reporting the true stress-true strain-birefringens. Strain cycling following steady deformation leads to near perfect chain orientation in crystalline domains while the amorphous chains relax. This morphology leads to substantial suppression of shrinkage.